Getting Connected: Experiential Dementia Skills Training. - Compton-Dooley, Pamela; Kyner, Marion; Little, Kimberly E. (Journal of Gerontological Nursing, 2025)
Purpose: Getting Connected: Experiential Dementia Skills Training, based on the Positive Approach to Care® model, was implemented to bridge the gap between knowledge and skills to determine whether nursing students feel more comfortable and prepared to care for persons living with dementia (PLWD). Method: The study examined the impact of experiential dementia skills training on nursing students' knowledge, comfort, and confidence when interacting with PLWD. The training was conducted at a 4-year pre-licensure, Bachelor of Science Nursing program in rural Southeast United States, where 62 sophomore students completed a 6-hour dementia skills training. Participation in the study was voluntary. Students were given pre- and posttests, with the dementia skills training serving as the intervention. Thirty-two students completed pre- and posttests, measuring knowledge, comfort, and confidence. Results: Findings showed the training enhanced students' knowledge of dementia and communication approaches; however, they did not feel more confident or comfortable interacting with PLWD immediately following the training. Conclusion: The Getting Connected: Experiential Dementia Skills Training using the Positive Approach to Care® model can be a useful approach for teaching nursing students about the lived experience of dementia and beneficial in helping them acquire knowledge and communication strategies for caring for PLWD. [Journal of Gerontological Nursing, 51(7), 21–24.]